Thermodynamic Differences of Different Friction Pairs in a Multidisc Clutch Caused by Spline Friction: Numerical Simulation and Experimental Verification. Issue 4 (4th July 2019) - Yu, Liang; Ma, Biao; Chen, Man; Li, Heyan; Zhang, Heng; Liu, Jikai
Abstract: Considering the spline friction, the dynamic model of a multidisc clutch is established that permits the calculation of the contact pressure and friction torque acting at each friction surface; the thermal model is then developed to investigate the temperature difference between different friction pairs. The corresponding test bench is established, where the effect of inertia on the torque error is analyzed in detail. The simulated and measured results are compared to validate the numerical model and confirm the existence of spline friction. The results indicate that spline friction can lead to the attenuation of contact pressure on friction pairs along the axial direction. Therefore, there exists a significant temperature gradient in the axial direction, and the maximum temperature appears in the second separate plate near the piston. Moreover, the friction torque of a single pair decreases along the axial direction. Thus, as the number of friction pair increases, the total friction torque increases nonlinearly, and the average torque of single friction pair decreases gradually.